Perusahaan Cacing Sabah / Farah Rasheeda Abil ... [et al.] - Abil, Farah Rasheeda; Ashmar, Hasmah; Francis, Kathleen; Sutarman, Suhaino (2010)
The world today is highly demanding on the natural resources as the earth is getting older. We prefer to produce product resources from natural environment compare using the product based on the chemical resources. Nowadays, the agriculture fields become develop from day to day. Therefore, the demands for soil fertilizer become increased. Therefore several steps are taken to cope with this matter. One of them is using our product as an alternative to replace other chemical fertilizer. Our company, Perusahaan Cacing Sabah (PERCASA), committed to grab this challenge that supplies our new product to our customers. Our product is a soil fertilizer agent that increases the soil nutrition. We guarantee our customers with high quality fertilizer. We produce our product by using the earth worm as the agent to produce this fertilizer. It is 100 percent organic without any chemical sources. We make sure that our worm is the best worm to produce this fertilizer. That is why we dare to say that our product is an environmental friendly product as we use only biological system to produce our product. We supply our product to the customers and provide delivering service depending on the distance of our customer's farm. We are really proud to develop our company to become one of the succeed company in Sabah thus entirely in Malaysia. For today, there is less number of competitors in this industry and this can become advantage to our company. This will give us a golden opportunity to develop the company economy with more firms. This industry also plays an important role in order to challenge the Sabah Development Corridor objectives. We are really confident that this industry can be able to give benefit and good profit to our company and also generally reduce the number of jobless people and also increasing the Sabah and also our country economy. Although our company is still young and lack of experience, we are really sophisticated to compete to other competitor to modernize and develop the agriculture industry.